The Effect of Sharia Business Unit Spin-Off Announcements on Stock Prices: A Case Study of CIMB Niaga Syariah and BTN Syariah - Fatikasari, Alfina; Astuti, Yuni (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to analyze the capital market’s reaction to the announcement of the Sharia Business Unit (UUS) spin-off policy at PT Bank CIMB Niaga Tbk (BNGA) and PT Bank Tabungan Negara (Persero) Tbk (BBTN), as well as to compare the market reaction patterns between the two issuers. This study employs a quantitative approach using the event study method. The market reaction is measured using abnormal returns calculated by the market model, with the Composite Stock Price Index (JCI) serving as a proxy for market returns. The observation period includes five days before and five days after the announcement date. The data used are in the form of daily closing stock prices, which are analyzed to obtain abnormal returns, average abnormal returns (AAR), and cumulative abnormal returns (CAR). The results of the study show that the spin-off announcements trigger different market reactions for each issuer. Shares of PT Bank CIMB Niaga Tbk (BNGA) exhibited a positive and statistically significant market reaction, while shares of PT Bank Tabungan Negara (Persero) Tbk (BBTN) exhibited a negative but not statistically significant reaction. These findings indicate that the capital market does not respond to spin-off policies uniformly, and that investor reactions are strongly influenced by the company’s internal preparedness as well as the clarity of managerial signals.